The proto-type basin and tectono-paleogeographic evolution of the Tarim basin in the Late Paleozoic - Xia, Jinkai; Zhong, Ziqi; Huang, Shaoying; Luo, Caiming; Lou, Hong; Chang, Haining; Li, Xiang; Wei, Lunyan (Frontiers in Earth Science, 2023)
The Tarim basin is a large composite and superimposed sedimentary basin that has undergone complex multi-period and polycyclic tectonic movements. Understanding the proto-type basin and tectono-paleogeographic evolution of this complex superimposed basin is important for understanding the basin-mountain coupling and dynamical mechanisms of the Paleo-Asian and Tethys tectonic systems as well as hydrocarbon exploration and development. Based on previous works, together with the recent exploration and geological evidences, three global plate tectonic pattern maps, four Tarim proto-type basin maps (in present-day geographic coordinates) and four regional tectono-paleogeography maps (in paleogeographic coordinates) during the Late Paleozoic are provided in this paper. Based on these maps, the proto-type basin and tectono-paleogeographic features of the Tarim basin during the Late Paleozoic are illustrated. The Devonian to Permian is an important period of terranes/island-arcs accretion and oceanic closure along the periphery of the Tarim block, and a critical period when the polarity of Tarim basin (orientation of basin long-axis) rotated at the maximum angle clockwise. During the Late Paleozoic, the periphery of the Tarim block was first collisional orogeny on its northern margin, followed by continuous collisional accretion of island arcs on its southern margin: on the northern margin, the North and South Tianshan Oceans closed from east to west; on the south-western margin, the Tianshuihai Island Arc gradually collided and accreted. These tectonic events reduced the extent of the seawater channel of the passive continental margin in the western part of the basin until its complete closure at the end of the Permian. The Tarim basin was thus completely transformed into an inland basin. This is a process of regression and uplift. The southwest of the Tarim basin changed from a passive to an active continental margin, through back-arc downwarping and eventually complete closure to foreland setting. The intra-basin lithofacies range from shelf-littoral to platform-tidal flat to alluvial plain-lacustrine facies. The tectonic-sedimentary evolution of the Tarim basin is strongly controlled by peripheral geotectonic setting.